Peran Masyarakat dalam Pengawasan Dana Desa - Made Beryl Ramadian Dwipayana; Kevin Adisputra; Revienda Anita Fitrie; Eva Hany Fanida (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The annual increase in Village Fund allocations has not been fully matched by optimal oversight. Data from Indonesia Corruption Watch (ICW) shows that cases of Village Fund misappropriation increased during the 2015–2017 period. One such problem occurred in Jeungjing Village, Cisoka District, Tangerang Regency, which experienced delays in submitting the 2017 Phase I Village Fund accountability report. This study aims to evaluate the role of the community in Village Fund oversight in Jeungjing Village. The study used a qualitative method with a case study approach in multiple units of analysis involving the village community, village officials, and supervisory institutions. Data were obtained through interviews, observations, and documentation studies, then analyzed using accountability theory through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that community oversight of Village Fund management is still suboptimal. Low levels of community understanding, minimal concern for oversight, and limited access to information are the main factors that contribute to weak community participation. These conditions have resulted in ineffective social control and accountability processes between the village government and the community